The influence of safety training, safety communication and safety knowledge towards safety participation among construction employees in China - Teng, Zhou (2025)
Safety participation has become an increasingly important issue in occupational safety and health domain, particularly among construction workers in China. Despite the critical contributions of construction sector to the Chinese economy in general, construction employees often focus more on general safety behaviors rather than safety participation. Therefore, this oversight could result to decreased poor safety practices, negatively affecting employees, employer and the nation as a whole. This study aims to explore the influence of safety training, safety communication, and safety knowledge on safety participation among construction employees in China. The theoretical framework is grounded in social exchange theory, emphasizing on the safety training, safety communication and safety knowledge provided by the organization in return for the employees’ safety participation. In order to evaluate these relationships, 115 construction workers completed a structured survey, and the data were analyzed using the Statistical Package for the Social Sciences (SPSS). The findings of this study revealed that safety communication and safety knowledge have a significant positive impact on safety participation, while safety training shows no significant effect on safety participation. In conclusion, this study highlights the need to integrate safety participation strategies within construction companies to enhance industry outcomes and improve employee’s safety at work